Frequency; of Prenatal Depression in Second and Third Trimesters of Pregnancy - Muhammad Muslim Khan, Fatima, Hemasa Gul, Sedra Tul Muntaha, Naila, Muhammad Kashif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prenatal depression is a mental disorder that develops during pregnancy. It is critical to detect depression during pregnancy and implement appropriate treatment techniques. Objective: The main objective of this study was to determine the frequency of prenatal depression in second and third trimesters of pregnancy Material and method: The present study was carried out at the department of Psychiatry and Department of Obstetrics and Gynecology, Bacha Khan Medical College Mardan Medical Complex Mardan from January 2022 to June 2022 after taking permission the ethical committee of the hospital. A total of 85 pregnant women during their 2nd (14-26 weeks) and 3rd (27-40 weeks) trimester of pregnancy who visited the out patients department (OPD) were included in this study. The data was collected by the process of administration of a questionnaire. Prenatal depression was identified using the Edinburgh Postnatal Depression Scale (EPDS). Depression was identified using a cutoff score of 12. The association between depression & age, parity, and pregnancy trimester was evaluated using the Chi-square test. Results: A total of 85 pregnant women were enrolled in the current study and interviewed out of which 61(71.7%) were in the 3rd trimester and 24(28.2%) were in the 2nd trimester. Mean age of the study participants were 25 years. 20(23.5%) were grand multipara 40(47.0%) women had more than one or less than four children and 25(29.4%) were primigravida. Majority 57(67.0%) of the individuals were in the age group 21 to 30 years. Edinburgh postnatal depression scale revealed that depression was seen in 30(35.2%) of the study participants. Among these depressed individuals, 6(25%) were in s 2nd and 25(40.9%) in 3rd trimester. Depression was most prevalent in Grand Multi 10(50%). Age wise distribution of depression revealed that the most effected age was above 30 years 4(50%).Only grandmulti-parity was substantially associated with prenatal depression on univariate analysis. Additionally, depression during the prenatal period has been correlated to greater age at pregnancy. Conclusion: The present study concluded that depression was most prevalent in the 2nd and 3rd trimesters of pregnancy (35%). But it was most common in the 3rd trimester. Keywords: Frequency; Prenatal depression; Trimester; Pregnancy.